Financial Distress Analysis of PT Samudera Indonesia Tbk - Mel Tanjung Khairatifah Rodi deni; Hendra Sastrawinata; Dwi Riana (Asean International Journal of Business, 2025)
This study uses the Zmijewski (X-Score) and Grover (G-Score) techniques to analyze PT Samudera Indonesia Tbk's financial hardship from 2018 to 2023. Working capital, liquidity, profitability, and solvency ratios were used to examine financial distress, which is a prelude to bankruptcy. Quantitative processing was done on secondary data from the Indonesian Stock Exchange and financial reports. Except for 2019, when the Grover technique identified distress because of pandemic-induced economic disruptions, the results indicated that PT Samudera Indonesia was primarily not in a position of financial distress. Stability was constantly shown by the Zmijewski technique, which demonstrated excellent liquidity and leverage management. Zmijewski's emphasis on solvency and Grover's emphasis on profitability are the causes of the discrepancy in the results. In addition to providing stakeholders with insights on financial risk assessment and mitigation in unpredictable markets, the findings demonstrate the company's resilience in the face of global difficulties such as trade wars and geopolitical crises.